Diabetes in the English-speaking Caribbean - Hennis, Anselm; Fraser, Henry S. (Revista panamericana de salud pública, 2004)
Rates of diabetes mellitus in the English-speaking Caribbean have been rising in recent years, and they are projected to continue climbing in the new millennium. Prevalence rates across countries of the African diaspora mirror levels of Western acculturation, and available data emphasize the importance of obesity as a modifiable risk factor. The population-based Barbados Eye Studies have provided new information about the burden of ocular complications of diabetes such as retinopathy and lens opacities. Diabetes was shown to increase the risk of lens opacities, and 14% of prevalent cataract was attributed to diabetes. Persons with type 1 diabetes were particularly at increased risk of retinopathy, as a result of longer durations of illness and poor glycemic control. Other Caribbean studies have suggested that glycemic control in patients evaluated in various clinical settings is suboptimal, which raises important concerns about quality of care. Diabetics are at increased risk of mortality compared with nondiabetics, and that mortality risk increases with higher baseline levels of glycosylated hemoglobin, even among nondiabetics. These data highlight the need for urgent attention to public health and clinical strategies to prevent diabetes in unaffected persons as well as to prevent or reduce the burden of complications among those who are affected. Among the measures that should be adopted to stem the flood of diabetes in the Caribbean region are lifestyle interventions to promote better nutrition and to increase exercise; patient education, particularly about the central role of diabetes self-management; and the multidisciplinary team approach in the provision of care.